Genotyping of Malaysian G6PD-deficient neonates by reverse dot blot flow-through hybridisation - Alina M.F.; Azma R.Z.; Norunaluwar J.; Azlin I.; Darnina A.J.; Cheah F.C.; Noor-Farisah A.R.; Siti-Hawa A.A.; Danny X.R.K.; Zulkifli N.F.; Ainoon O. (Springer Nature Publishing Group, 2024)
Indexed by WOS/Scopus/ERA